PENDIDIKAN ISLAM DI KERAJAAN TURKI USMANI - Saat, Sulaiman (Hunafa: Jurnal Studia Islamika, 2011)
Abstract: The kingdom of the Ottoman Turk was one of the Islamic kingdoms very influential in Europe lands in around the thirteenth century until the fifteenth century A.D. During its rule, the Ottoman Turk had no great concern to the development of education compared with political sector. Consequently, the Islamic education during the rule of the kingdom left behind. For about seven centuries of its rule, the Ottoman Turk  produced no influential scientist in Islamic word. The backwardness in the field of education and the expansion as well as the corruption of the ruler’s morality brought about the disability of the kingdom to oppose  the Western attack with modern arm forces as the result of their technological engineering.  Kata Kunci: pendidikan Islam, Kerajaan Turki Usmani